تأثير إضافة الفيلر على خصائص البيتون المرصوص بالدحي - علي خيربك; بسام سلطان; نعمى ديوب (Tishreen University, 2016)
يقدم البيتون المرصوص بالدحي (RCC) مفهوماً مختلفاً في إنشاء الرصف والسدود فهو بيتون جاف (هبوط أبرامز معدوم), ذو محتوى مائي منخفض، ومزيج كثيف يتضمن حصويات متدرجة الخشونة, ومواد إسمنتية رابطة وماء. مما يجعل من رصه بسماكات كبيرة أمراً صعباً بدون استخدام الرجاجات ذات الطاقة الكبيرة. ينقل هذا البيتون بالشاحنات, ويوضع ويرص باستخدام معدات الرصف الإسفلتي. تكمن الفائدة الرئيسية لهذه التقنية في تخفيض زمن الإنجاز والتوفير في كلف العمل وإمكانية الاستعاضة عن المواد التقليدية في الرصف الطرقي. كما يؤمن سطحاً متيناً ومصقولاً وأملساً من شأنه تسهيل عمليات المرور المتوقعة في كل الظروف والعوامل المختلفة كالحمل المحوري والشروط البيئية. يقدم هذا البحث تكنولوجيا جديدة لصناعة عينات البيتون المرصوص بالدحي بتطبيق آلية الرج-الضغط Vibro-compaction بشكل متتال على العينات البيتونية الطرية. تم تصنيع عينات بيتونية مخبرياً تختلف بمحتواها من الفيلر الكلسي, وبعد إجراء الدراسة التحليلية لنتائج اختبارات هذه العينات تم التوصل إلى المحتوى المثالي للفيلر لهذا النوع من البيتون وذلك باعتماد المقاومة على الضغط البسيط وسرعة تطورها مع الزمن كمعيارين أساسيين للتصميم.   The Roller Compacted Concrete (RCC) offers a different concept in the creation of pavement and concrete dams it's dry Beaton (Zero Abrams slump), with a low water content, and includes of dense mix consisting of graded coarse aggregate, and cementations materials, and water, this makes it so difficult  to compact it in big thicknesses layers without using  large energy rollers compactors. concrete conveys by trucks, placed and compacted by using equipment asphalt pavement. The main advantage of this technique is in reducing the completion time and cost savings in labor and the possibility of replacing traditional materials in road paving. It also provides a solid surface smooth and polished, and would facilitate the operations of traffic expected in all circumstances and various factors such as axial loads and environmental conditions. This paper presents a new technology for the manufacture of Roller compacted concrete samples by applying a mechanism of Vibro-compaction pressure on samples of fresh concrete. It had Been manufactured concrete samples differ from their limestone filler content, and after conducting an analytical study of the results of tests of these samples has been reached to ideal feller content for this type of concrete by reliance on the mechanical strength and speed of evolution with time as criteria for the basic design.